The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1002/nano.202000140
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen‐doped porous biomass carbon with ultrastable performance as anodes for potassium‐ion batteries

Abstract: The potential safety hazards and limited lithium resources of lithium‐ion batteries (LIBs) have restricted their practical application. Potassium‐ion batteries (KIBs) are a novel energy storage technology with great cost advantages and are a promising alternative to LIBs. However, because of the large ionic radius of K+, the common anode materials used in LIBs exhibit a large volumetric expansion and structural collapse in the process of charging and discharging in a KIB. In this work, the prepared nitrogen‐do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 47 publications
(37 reference statements)
0
6
0
Order By: Relevance
“…[151,152] M a X b materials provide the required "vacancies" for the insertion of Li + in the process of discharging. [153] The valence of a certain element in M a X b can be changed due to the Li + insertion and extraction process, while the structural [48,[78][79][80][81][82][83][84] The performance improvement diagrams of BDC-based materials in b) LIBs, [79,80,[85][86][87][88][89][90][91][92][93][94][95] c) SIBs, [8,81,[96][97][98][99][100][101][102][103] and d) KIBs [104][105][106][107][108][109][110][111][112][113] in recent years. e) Comparison of LIBs, SIBs, and KIBs.…”
Section: Alloying Reaction Electrode Materialsmentioning
confidence: 99%
See 4 more Smart Citations
“…[151,152] M a X b materials provide the required "vacancies" for the insertion of Li + in the process of discharging. [153] The valence of a certain element in M a X b can be changed due to the Li + insertion and extraction process, while the structural [48,[78][79][80][81][82][83][84] The performance improvement diagrams of BDC-based materials in b) LIBs, [79,80,[85][86][87][88][89][90][91][92][93][94][95] c) SIBs, [8,81,[96][97][98][99][100][101][102][103] and d) KIBs [104][105][106][107][108][109][110][111][112][113] in recent years. e) Comparison of LIBs, SIBs, and KIBs.…”
Section: Alloying Reaction Electrode Materialsmentioning
confidence: 99%
“…[48,[78][79][80][81][82][83][84] Many studies have been reported by using BDC as an important part of batteries. [50][51][52][53][54][55][56][57][58][59][60] To better understand the research progress of BDC, we summarized the performance improvement diagrams of BDC-based materials in LIBs (Figure 1b), [79,80,[85][86][87][88][89][90][91][92][93][94][95] SIBs (Figure 1c) [8,81,[96][97][98][99][100][101][102][103] and KIBs (Figure 1d) [104][105][106][107][108]…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations